Fracture initiation and propagation of supercritical carbon dioxide fracturing in calcite-rich shale: A coupled thermal-hydraulic-mechanical-chemical simulation - Wu, Lin; Hou, Zhengmeng; Xie, Yachen; Luo, Zhifeng; Xiong, Ying; Cheng, Long; Wu, Xuning; Chen, Qianjun; Huang, Liangchao (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2023)
The initiation and propagation mechanisms of supercritical carbon dioxide (scCO2) fracturing are more complex than those of hydraulic fracturing in calcite-rich shale due to the temperature‒pressure sensitivity of scCO2 and scCO2-brine-rock interactions. In this study, we present an enhanced thermal-hydraulic-mechanical-chemical (THMC) simulator called CMPSF, which incorporates a rock damage model and a CO2 physical property model into the COMSOL-MATLAB-PHREEQC (CMP) coupling framework via MATLAB. Furthermore, the coupling procedure of CMPSF is optimized from a previous sequential non-iterative approach to a sequential partly-iterative approach. We then utilize CMPSF validated with numerical and experimental examples to analyze the evolution of THMC fields and examine the impact of calcite content and injection temperature on fracture initiation and propagation of scCO2 fracturing in calcite-rich shale. The simulation results reveal that the decreased mass fraction of calcite is 1.5‰ and the porosity increment from calcite dissolution is 0.33‰ at most within 12 min. A higher calcite content and injection temperature lead to a decrease in fracture initiation pressure and an increase in rock damage ratio. Specifically, as the calcite content increases from 50 wt% to 80 wt%, the fracture initiation pressure decreases by 0.1 MPa, and the final damage ratio increases by 0.25%. As the injection temperature increases from 30 °C to 60 °C, the fracture initiation pressure decreases by 4.3 MPa, and the final damage ratio increases by 1.55%. Calcite dissolution has a minor impact on fracture initiation and propagation at the early stage of scCO2 fracturing only from the perspective of affecting seepage, and its long-term effects require further investigation. Our findings provide insight into the complex THMC coupling processes of scCO2 fracturing in calcite-rich shale.